2018
DOI: 10.1590/1806-93042018000100009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rs1800469 and rs1800468 Polymorphisms of the TGF-β1 Gene in Women with Pre-eclampsia

Abstract: Objectives: to verify the contribution of polymorphisms rs1800469 and rs1800468 of the TGF-β1 gene and the risk factors for the pre-eclampsia development.Methods: this is a case-control study with 257 women from the Uberaba region of Minas Gerais were selected, 88 of them were in the pre-eclampsia group and 169 in the control group. Genotyping was performed by allelic discrimination using the real-time PCR technique. The odds ratio and the 95% confidence interval were used to evaluate the probability of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…After application of the criteria, 14 studies were kept (Figure 1). Characteristics of the 11 studies are shown in Table 1 13–26 . The published year ranged from 2006 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…After application of the criteria, 14 studies were kept (Figure 1). Characteristics of the 11 studies are shown in Table 1 13–26 . The published year ranged from 2006 to 2019.…”
Section: Resultsmentioning
confidence: 99%